2014
DOI: 10.1038/bcj.2014.29
|View full text |Cite
|
Sign up to set email alerts
|

The role of epigenetics in the biology of multiple myeloma

Abstract: Several recent studies have highlighted the biological complexity of multiple myeloma (MM) that arises as a result of several disrupted cancer pathways. Apart from the central role of genetic abnormalities, epigenetic aberrations have also been shown to be important players in the development of MM, and a lot of research during the past decades has focused on the ways DNA methylation, histone modifications and noncoding RNAs contribute to the pathobiology of MM. This has led to, apart from better understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 101 publications
0
87
0
Order By: Relevance
“…P values were calculated using ANOVA compared with vehicle ( Ã , P 0.05; ÃÃ , P 0.01 and ÃÃÃ , P 0.001). (33). We uncovered an antiproliferative activity of EZH2 inhibition in vitro in a set of multiple myeloma cell lines and translated these findings to an in vivo xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…P values were calculated using ANOVA compared with vehicle ( Ã , P 0.05; ÃÃ , P 0.01 and ÃÃÃ , P 0.001). (33). We uncovered an antiproliferative activity of EZH2 inhibition in vitro in a set of multiple myeloma cell lines and translated these findings to an in vivo xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs, key enzymes regulating the acetylation status of both histone-and non-histone proteins, are classified into 4 classes: class I (HDAC1, 2,3,8), class IIa (HDAC4, 5, 7, 9) and class IIb (HDAC6,10), class-III (SIRT1-7), and class-IV (HDAC11; ref. 12).…”
Section: Introductionmentioning
confidence: 99%
“…A number of epigenetic modifications have been so far linked to cancer, including posttranslational modification of histones, DNA methylation, and the most recently discovered noncoding RNAs, which are currently considered key determinants in human cancer pathogenesis (2). In the last few years, a wealth of studies has shown deep dysregulation of miRNAs in human cancers, including multiple myeloma (3).…”
Section: Introductionmentioning
confidence: 99%